Giant retroperitoneal liposarcoma: report of a rare case - Pal, Subrata; Sengupta, Sanjay; Biswas, Biplab Kr; Jana, Sritanu (International Journal of Research in Medical Sciences, 2017)
Retroperitoneal liposarcoma is an uncommon malignant mesenchymal tumour of adipocytic differentiation. Giant retroperitoneal liposarcoma is a rare entity which achieves such a large tumour bulk without any significant clinical symptoms due to deep seated location of the tumour. Though incidence of distant metastasis is less but local recurrence is fairly common. Surgical management is the key of management in retroperitoneal liposarcoma in spite of its large size and local invasion to vital organs. We are reporting a case of giant retroperitoneal liposarcoma of 27.5 Kg in a 45 year old female patient.